Leading your team : how to involve and inspire teams - Leigh, Andrew; Maynard, Michael (Sonoma, Calif : Nicholas Brealey, 1995)
This book presents how to involve and inspire teams on leading.
Keywords: Leadership; Workplace; Leadership; Teams in the workplace